Fenomena Ziarah Haji (Studi Tentang Soloidaritas Masyarakat di Desa Podorejo Kecamatan Sumbergempol Kab. Tulungagung) - Hanum Khumeidatul Khasanah; A Zahid (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research discusses the tradition of the Hajj pilgrimage, where people come to visit people who have just returned from the Hajj, not someone visiting the holy land of Mecca, and also discusses community solidarity when the Hajj pilgrimage tradition takes place. The method used in this research is a qualitative research method with a phenomenological approach. With two research results, namely: (1) Knowing the meaning of the Hajj pilgrimage tradition, where in this tradition it is not people who visit the holy land but visits of people who have just returned from the Hajj with a specific purpose; (2) Know the forms of solidarity in the form of mutual cooperation and mutual assistance activities during the traditional Hajj pilgrimage activities